#TITLE_ALTERNATIVE# - Sumantri (NIM 107 03 048), Natalia
ABSTRACT : Spectrofluorometric method has been applied for determination of vitamin C in fruits juice based on measurement of decreasing fluorescence intensity of methylene blue due to its reaction with vitamin C, at excitation of 664nm and emission of 670nm. This method had the recovery of 90-120%, coefficient of variation of 2.69 - 10.42% , and limit of detection of 5.67x10 - 8 mol/L. This method was influenced by the presence of heavy metals, acidity, and glucose. The content of vitamin C (%b/b) in several fruits juice which were starfruit, lemon, and lime were in a range of 0.019 +/- 0.002 to 0.041 +/- 0.006%. The spectrofluorometric method for determination of vitamin C in fruits juice was compared to iodimetric method.